Sistem Permohonan Cuti Karyawan untuk Kantor DPRD Provinsi Sumatera Utara - Tumanggor, Ahmad AlfanSori; Aulia, Nurul (Jurnal Media Teknik Elektro dan Komputer, 2025)
This research focuses on designing a web-based employee leave application system for the Wasbang Room at the North Sumatra Provincial DPRD Office. The goal is to develop a system that improves the efficiency of managing leave requests by simplifying the application process, accelerating data processing, providing transparent access to leave balances, and generating reports more effectively for leadership through centralized database storage. The system design is modeled using Unified Modeling Language (UML), specifically use case diagram, to illustrate system functionality and user interactions. The web-based platform allows access for employees, supervisors, and administrators with role-based access control. System functionality is tested using the black box testing method, focusing on core features such as login, employee data input, leave submission, leave approval, administrative data management, and leave history tracking. Test results confirm that all features operate according to the expected scenarios and that the system provides appropriate validation feedback for invalid inputs. This system has proven to enhance the speed and accuracy of the leave approval process, reduce the risk of manual data loss, and improve the accountability of personnel records. The novelty of this research lies in its integrated design approach, which incorporates organizational authorization flows and traceable leave documentation accessible by administrators. Overall, this study demonstrates the value of web-based information systems in optimizing administrative processes. The proposed solution is functional, user-friendly, and adaptable to other organizations with similar administrative needs. It is expected to support data-driven managerial decision-making and accelerate the digital transformation of personnel systems.